SOFT INTERSECTION h-IDEALS OF HEMIRINGS AND ITS APPLICATIONS: Soft set - Ma, Xueling; Zhan, Jianming (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we introduce a new kind of soft hemirings called soft intersection hemirings and obtain some related properties. Some basic operations are also investigated. Finally, we describe some characterizations of h-hemiregular hemirings by means of SI-h-ideals.